Exploring omics strategies for drug discovery from Actinomycetota isolated from the marine ecosystem - Manik Prabhu Narsing Rao; Syed Raziuddin Quadri; Manda Sathish; Ngoc Tung Quach; Wen-Jun Li; Wen-Jun Li; Arinthip Thamchaipenet; Arinthip Thamchaipenet (Frontiers in Pharmacology)
Marine Actinomycetota are prolific producers of diverse bioactive secondary metabolites, making them vital for drug discovery. Traditional cultivation and bioassay-guided isolation techniques often lead to the rediscovery of the same compounds, revealing the limitations of these traditional approaches and emphasizing the need for more advanced methods. The emergence of omics technologies such as genomics, metagenomics, transcriptomics, and metabolomics has dramatically enhanced the ability to investigate microorganisms by providing detailed insights into their biosynthetic gene clusters, metabolic pathways, and regulatory mechanisms. These comprehensive tools facilitate the discovery and functional analysis of new bioactive compounds by revealing the genetic blueprints underlying their biosynthesis. Omics and function-driven techniques like heterologous expression, analytical techniques (including high-resolution mass spectrometry and nuclear magnetic resonance spectroscopy), and culture condition optimization have enabled access to previously silent or cryptic gene clusters, expanding the chemical diversity available for exploration. This review emphasizes the integration of omics-based insights with function-driven methodologies and innovative culture techniques, forming a holistic approach to unlock the extensive biosynthetic capabilities of marine Actinomycetota. Combining these strategies holds great promise for discovering new marine-derived compounds with potential therapeutic applications.